2001
DOI: 10.1016/s0006-3495(01)76222-4
|View full text |Cite
|
Sign up to set email alerts
|

Stretching a Macromolecule in an Atomic Force Microscope: Statistical Mechanical Analysis

Abstract: We formulate the proper statistical mechanics to describe the stretching of a macromolecule under a force provided by the cantilever of an Atomic Force Microscope. In the limit of a soft cantilever, the generalized ensemble of the coupled molecule-cantilever system reduces to the Gibbs ensemble for an isolated molecule subject to a constant force in which the extension is fluctuating. For a stiff cantilever, one obtains the Helmholtz ensemble for an isolated molecule held at a fixed extension with the force fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 12 publications
2
51
0
Order By: Relevance
“…Strictly, neither the Gibbs ensemble (no force fluctuations) nor the Helmholtz ensemble (no distance fluctuations) is correct, and one has to find a proper statistical analysis of a system with constant spring constant. [124,125] However, it has been found that, in the soft cantilever regime (which applies to the usual experimental conditions), the Gibbs ensemble is a good approximation. Based on this, the well-accepted concept of entropic elasticity manifests itself in an effective restoring force upon stretching (or compressing) a flexible polymer chain by an external force field as a result of a loss in conformational freedom.…”
Section: Stretching Of Single Polymer Chainsmentioning
confidence: 99%
“…Strictly, neither the Gibbs ensemble (no force fluctuations) nor the Helmholtz ensemble (no distance fluctuations) is correct, and one has to find a proper statistical analysis of a system with constant spring constant. [124,125] However, it has been found that, in the soft cantilever regime (which applies to the usual experimental conditions), the Gibbs ensemble is a good approximation. Based on this, the well-accepted concept of entropic elasticity manifests itself in an effective restoring force upon stretching (or compressing) a flexible polymer chain by an external force field as a result of a loss in conformational freedom.…”
Section: Stretching Of Single Polymer Chainsmentioning
confidence: 99%
“…In derivation of this formula the force f was considered as an independent variable (the isotensional boundary conditions [9,10] ). The formula accurately represents the small and large force regime but has a maximum error of 10% in the intermediate force regime.…”
Section: Single-chain Elastic Functionsmentioning
confidence: 99%
“…In general, the controlled position scenario has finite force fluctuations. 15,16 These become particularly important when the polymer spacer is pulled very fast and equilibrium theories become inapplicable. In such a scenario, one might consider an approach as outlined elsewhere.…”
Section: ͑21͒mentioning
confidence: 99%